Organized Capitalism and Organized Science - Jürgen Kocka (European Review, 2024)
This article compares two different ways in which German industries, during the half century before 1914, managed to integrate useful results from scientific research: At the time, on the one hand there was single-firm-based industrial research, and on the other the cooperation of science, business, and government in the Emperor William Society for the Advancement of Sciences (1911) out of which, after the Second World War, the Max Planck Society emerged. On this basis, the article discusses similarities and tensions between capitalism and the sciences which, in spite of some structural similarities, follow different logics.
Keywords: 320